Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T14:57:33+01:00
A) 3(a+b)+(a-2b)=3a+3b+a -2b=4a+b
b) -4(x-z)-(x+y)=-4x+4z-x-y=-5x+3z
c) 5(4x-7)+(7-4x)=20x-35+7-4x=16x-28
d) (4x-y)-2(x+y)=4x-y-2x-2z=2x-3z
e) 2(3x-2y+3z)-5(x-y-z)=6x-4y+6z-5x+5y+5z=x+y+11z
f) 4x(x-y-z)-2x(4x-y+z)=4x2-4xy-4xz-8x2+2xy-2xz=-4x2-2xy-6xz
2--->kwadrat
g) -3x^2(x-2/3y)+5x(x^2-7xy)=-6x2+4y+10x2-35xy=4y-35xy+4x2
h) -2<pierwiastek z 2>(a+<pierwiastek z 2>b)-4(a<pierwiastek z 2>-2b)
2009-11-17T15:00:17+01:00
A)3a+3b+a-2b=4a-b
b)-4x+4z-x-y=-5x+4z-y
c)20x-35+7-4x=16x-28
d)4x-y-2x-2y=2x-3y
e)6x-4y+6z-5x+5y-5z=x+y+z
f)4x<kwad>-4xy-4xz-8x<kwad>-2xy+2xz=4x<kwad>-6xy-2xz
dalej nie wiem:((
  • Użytkownik Zadane
2009-11-17T15:02:09+01:00
A.3a+3b+a-2b=4a+1b
B.-4x+4z-x-y= -3x+4z-y
C.20x-35+7-4x=16x-42
D.4x-y-2x-y=2x-2y
E.6x-4y+6z-5x+5y+5z=1x-1y+11z
F.4x do potęgi drugiej-4xy-4xz-8xdo potęgi drugiej +2xy-2xz=-4x do potegi drugiej-(-2xy)-(-6xz)